2020
DOI: 10.1159/000505952
|View full text |Cite
|
Sign up to set email alerts
|

Tea Consumption Is Associated with Decreased Disease Activity of Rheumatoid Arthritis in a Real-World, Large-Scale Study

Abstract: Introduction: The role of tea consumption on rheumatoid arthritis (RA) has been studied in recent years, but no clear conclusion has been drawn as a result of small sample size of the studies or the fact that only in vitro studies have been performed. Objectives: The aim of this study was to explore the possible association of tea consumption with RA through a large-scale, real-world study. Methods: A total of 733 RA patients were investigated from June to December, 2016. The disease activity of RA was assesse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 32 publications
0
6
0
Order By: Relevance
“…However, a case-control study in Iran showed an inverse association between tea consumption and the risk of RA (18). Similarly, Jin et al, in a cross-sectional study on RA patients, found an inverse association between high tea consumption (>750 mL/day) and disease severity in patients with RA (56). A number of studies have also shown that tea consumption could have a beneficial effect on inflammatory factors which is due to catechins and other flavonoids (57,58).…”
Section: Discussionmentioning
confidence: 96%
“…However, a case-control study in Iran showed an inverse association between tea consumption and the risk of RA (18). Similarly, Jin et al, in a cross-sectional study on RA patients, found an inverse association between high tea consumption (>750 mL/day) and disease severity in patients with RA (56). A number of studies have also shown that tea consumption could have a beneficial effect on inflammatory factors which is due to catechins and other flavonoids (57,58).…”
Section: Discussionmentioning
confidence: 96%
“…Green tea is a very popular beverage consumed daily worldwide and green tea extracts are often used in different dietary supplements. Very recently, a large cohort study, which included 733 RA patients, demonstrated that subjects consuming higher amount of tea (>750 mL/day) were associated with lower RA disease activity, suggesting the potential beneficial effect of tea [25]. However, in a similar study, based on the Women's Health Initiative Observational Study cohort (185 women self-reporting validated cases of RA observed for 3 years), only a small association between daily caffeinated, non-herbal tea consumption and incident RA was observed [26].…”
Section: Discussionmentioning
confidence: 99%
“…EGCG, quercetin, resveratrol, p -coumaric acid, luteolin, curcumin, kaempferol and apigenin are the most effective polyphenols against arthritis ( Ahmed et al, 2006 ; Pragasam, 2012 ; Riegsecker et al, 2013 ; Abba et al, 2015 ; Chang et al, 2015 ; Daily et al, 2016 ; Aziz et al, 2018 ). Tea flavan-3-ols like EGCG are useful in RA ( Jin et al, 2020 ). The effects of quercetin on disease severity and inflammation in women with RA showed considerably decreased early morning stiffness and discomfort and after-activity pain ( Javadi et al, 2017 ).…”
Section: Polyphenols and Their Protective Effects Against Human Diseasesmentioning
confidence: 99%